RANCANG BANGUN DAN PEMBUATAN MEJA PUTAR MEKANIS··ELEKTRIS UNTUK MENINGKA TKAN KUANTITAS DAN KUALITAS PRODUKSI PENGRAJIN KERAMIK - Puspito, Jarwo; Widarto, Widarto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The goal of this activity is design and manufacturing Rotating Table Machine for Ceramics  Handy  Craft. The  construction  simple  relatively, portable,  simple  technology, and simple operation.The  Methodology  that   used  is  design  and  manufacturing   method  that  cover geometric  modeling,  analysis,  synthesis  and  evaluation,  working  drawing  and manufacturing continually.The result of this program is manufacturing Rotating Table Machine for Ceramics Handy Craft.  The specification of machine is 110 em length x 70 ern wide x 90 em high. The prime mover is electrical   DC motor 20 Volt,  10 Amphere. The working capacity of this machine is the work piece that 300 mm diameter and 550 rnm high. The functional test result that the machine element is good function and the service test result that the machine is easy service.  Profit  Different    no-vucer  and vucer  is significant  and base economics analysis the Break Even Point (BEP) of machine is 15 month.Key word:   rotating  table  machine,  and   ceramics.